Perilaku Stereotip Harimau Sumatera (Panthera tigris sumatrae) Dalam Masa Rehabilitasi Pada Pusat Rehabilitasi Harimau Sumatera Dharmasraya (Pr-Hsd) Arsari Sumatera Barat: Stereotypical Behavior of Sumatran Tiger (Panthera tigris sumatrae) During the Rehabilitation Period at The Sumatran Tiger Rehabilitation Center Dharmasraya (PR-HSD) ARSARI Sumatera Barat - Wulan, Cory; Putri, Nia; Khabibi, Jauhar (Fakultas Kehutanan Universitas Jambi, 2022)
ABSTRACT Animal activity is an activity carried out by animals consisting of several behaviors. Behavior is animal movements that are influenced by the relationship between the animal and its environment that occurs repeatedly, so that it becomes a characteristic of the animal. During the rehabilitation period, animals experience changes in their habitat and other behavioral changes. This study aims to analyze the stereotypical activity of the Sumatran tiger (Panthera tigris sumatrae) during the rehabilitation period at the Sumatran Tiger Rehabilitation Center which is included in the Appendix I category in CITES with critically endangered status causing (Panthera tigris sumatrae) to be conserved ex-situ. Research on stereotypical activities of Sumatran tigers was conducted at the ARSARI Sumatran Tiger Rehabilitation Center (PR-HSD) in West Sumatra. The object of this research is a male tiger (Putra Singgulung) and a tigress (Ria). The method used is focal animal sampling. The results obtained in a study of the stereotypical activity of two Sumatran tigers in ex-situ habitat at PR-HSD were female Sumatran tigers (35.25%) and male Sumatran tigers (36.21%) (Putra singgulung). The most frequently seen activities were resting behavior (55.88%) in female Sumatran tigers (Ria) and (55.88%) in male Sumatran tigers (Putra singgulung). Research on stereotypical Sumatran tiger activities is expected to become basic data for the conservation management of the Sumatran tiger (Panthera tigris sumatrae) at the Dharmasraya Sumatran Tiger Rehabilitation Center (PR-HSD) ARSARI, West Sumatra. Â Keywords: sumatran tiger (panthera tigris sumatae), ex-situ conservation, stereotyping activity Â ABSTRAK Aktivitas satwa merupakan kegiatan yang dilakukan oleh satwa terdiri dari beberapa perilaku. Perilaku merupakan gerak-gerik hewan yang dipengaruhi oleh hubungan antara hewan dengan lingkungannya yang terjadi berulang-ulang, sehingga menjadi ciri dari satwa tersebut. Pada masa rehabilitasi satwa mengalami perubahan habitat dan perubahan perilaku lainnya. Penelitian ini bertujuan untuk menganalisis aktivitas stereotip harimau sumatera (Panthera tigris sumatrae) dalam masa rehabilitasi pada Pusat Rehabilitasi Harimau sumatera termasuk dalam kategori Appendix I dalam CITES dengan status critically endangered menyebabkan (Panthera tigris sumatrae) dikonservasi secara ex-situ. Penelitian tentang aktivitas stereotip harimau sumatera dilakukan pada Pusat Rehabilitasi Harimau Sumatera Dharmasraya (PR-HSD) ARSARI Sumatera Barat. Objek pada penelitin ini yaitu seekor harimau jantan (Putra Singgulung) dan seekor harimau betina (Ria). Metode yang digunakan yaitu focal animal sampling. Hasil yang didapatkan pada penelitian mengenai aktivitas stereotip dua harimau sumatera pada habitat ex-situ di PR-HSD yaitu pada harimau sumatera betina (Ria) (35.25%) dan (36.21%) harimau sumatera jantan (Putra singgulung). Aktivitas aktivitas yang paling sering terlihat yaitu perilaku istirahat (55.88%) pada harimau sumatera betina (Ria) dan (55.88%) pada harimau sumatera jantan (Putra singgulung). Penelitian aktivitas stereotip harimau sumatera diharapkan menjadi data dasar untuk manajemen konservasi harimau sumatera (Panthera tigris sumatrae) di Pusat Rehabilitasi Harimau Sumatera Dharmasraya (PR-HSD) ARSARI Sumatera Barat. Â Kata kunci: harimau sumatera (Panthera tigris sumatrae), konservasi ex-situ, aktivitas stereotip